A Comparative Study of Non Descent Vaginal Hysterectomy and Total Abdominal Hysterectomy - Jebu, Jebunnesa; Haque, Nadira; Lucky, Shamsunnahar; Debnath, Keya (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Hysterectomy is the commonest major surgical procedure in gynecology. There are different approaches to perform hysterectomy. Conventional abdominal and vaginal hysterectomies are considered to be the common gynecological operations. This study was carried out to assess the comparison between total abdominal hysterectomy and non-descent vaginal hysterectomy. Materials and methods: This randomized clinical trial study was conducted in the department of Obstetrics and Gynecology, Khulna Medical College Hospital between I st July 2021 and 31 st December 2021. A total of 60 patients who admitted in the indoor facilities of the department of Obstetrics and Gynecology, Khulna Medical College Hospital for hysterectomy was considered as study population. Among them 30 were in group A (On whom total abdominal hysterectomy was conducted) and another 30 were in group B (On whom non descent vaginal hysterectomy was conducted). The patients having benign uterine pathology, mobile uterus where uterine size was within 14 weeks were included for the study. All operations were performed by expert gynecological surgeon along with his/her assistants. A comparative study was made between group A and B in terms of duration of Surgery, intra-operative complications, time of ambulation. post-operative complications and duration of hospital stay. All the data was recorded in a preformed questionnaire. Results: The mean age was 44.63±6.24 (SD) years and 47.87±6.64 (SD) years in group A and group B. Greater part of the respondents from group A had >12 weeks’ uterus. From group B 26.7% had normal uterus and 26.7% had 8 weeks’ uterus which was the majority.The most common indication for group A was adenomyosis (36.7%) followed by abnormal uterine bleeding (26.7%), fibroid (26.7%) and PID (10.0%).For group B, the most common indications was abnormal uterine bleeding 946.7%) followed in decreasing order adenomyosis (26.7%), fibroid (23.3%) and PID (3.3) duration of surgery was 91.03±10.64 (SD) minutes for group A patients and 65.83±10.25 (SD) for group B patients. A statistically significant difference was observed between groups where longer surgery duration was observed in group A (p<0.05). Intraoperative blood loss was also significantly higher in group patients (215±39.17 ml Vs 167.07±25.14 ml). The mean days required before ambulation was 2.3±0.8(SD) days for group A and 1.2±0.5(SD) days for group B. Incidence of post-operative complications were significantly higher in group A (p<0.05). Post-operative complications were fever (30.0% in group A and 26.7% in group B), UTI (16.7% in group A and 10% in group B), RTI (23.3% in group A and 16.7% in group B), wound infection (16.7% in group A). Conclusion: NDVH operation is a less invasive operation which is associated with less time duration, minimal blood loss, limited requirements of blood transfusion, minimal per-operative and postoperative complications, early ambulation and short duration of hospital stay. JCMCTA 2025 ; 36 (1) : 66-70